PENGELOLAAN KEWIRAUSAHAAN PONDOK PESANTREN HIDAYATUS SAALIKIN DESA PEMBUANG HULU KABUPATEN SERUYAN - Dilla Sofya; Sardimi Sardimi; Musyarafah Musyarafah (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Economic development in Indonesia still faces various challenges, particularly in creating job opportunities and fostering an entrepreneurial spirit. Islamic boarding schools (pesantren) hold great potential in developing entrepreneurship through the cultivation of students' independent and religious character. This study aims to describe the implementation of entrepreneurship management at Pondok Pesantren Hidayatus Saalikin, located in Pembuang Hulu Village, Seruyan Regency. The research uses a descriptive qualitative approach, with data collection techniques including documentation, observation, and interviews. Data analysis involves the stages of data collection, data reduction, data presentation, and drawing conclusions. The focus of the study includes aspects of planning, organizing, actuating, and controlling entrepreneurial activities. The findings indicate that although entrepreneurial activities have shown progress, their implementation still faces obstacles such as limited human resources and internal policies of the pesantren that restrict students' direct involvement. This research is expected to serve as a reference in formulating entrepreneurial management strategies in pesantren to strengthen the economic independence of the Muslim community